Developing online module uses online application - Oktha Ika Rahmawati; Fitri Nurdianingsih; Andri Andri (Universitas Muhammadiyah Semarang, 2022)
This study aims to develop online digital module by using Heyzine online application. The method used was simple ADDIE model of RnD. The object of this study was grammar and the subject was the second semester of english department students in IKIP PGRI Bojonegoro. The module prototype made based on the result of RPS analysis and then it was uploaded to the application. The result showed that the module was eligible to be used in the class with the value are 83% for the media effect, 83.3% for instruction, and 60% for design from the experts. Meanwhile from the students are 86,7% for media effect, 80% for instruction, and 86,7 % for design.